2015
DOI: 10.1093/jisesa/iev129
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation Into the Colonization of Concealed Cadavers by Necrophagous Blowflies

Abstract: We used seven baited boxes with different combinations of access holes and odor diffusion surfaces to study the arrival of necrophagous flies. During laboratory experiments, 30 gravid Lucilia sericata females were kept in a chamber with one of the boxes. The box with the largest odor diffusion surface (99 cm2) combined with the lowest accessibility (one 1 cm2 entrance hole) was entered least (5 ± 3.7 flies per run). In contrast, the most frequently entered box (one 9 cm2 entrance hole with no additional odor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Traps baited with decaying marine fish flesh captured the most individuals, whereas traps baited with decaying pig liver typically attracted the least. This largely consistent pattern of relative preferences for different sources of odour has not been widely reported for carrion flies in natural populations, perhaps reflecting the more typical forensic entomological research focus on how oviposition behaviour is influenced by variation in the characteristics of the same carcass species (Archer & Elgar, 2003a,b; Gião & Godoy, 2007; Gunn & Bird, 2011; Yang & Shiao, 2012; Charabidze et al, 2015; Gunn, 2016; Martin & Verheggen, 2018; but see Bunchu et al, 2008). We also found that individuals of L. sericata and an unidentified platystomatid collected from the traps baited with pig liver tended to have longer antennae than those collected from the other traps.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Traps baited with decaying marine fish flesh captured the most individuals, whereas traps baited with decaying pig liver typically attracted the least. This largely consistent pattern of relative preferences for different sources of odour has not been widely reported for carrion flies in natural populations, perhaps reflecting the more typical forensic entomological research focus on how oviposition behaviour is influenced by variation in the characteristics of the same carcass species (Archer & Elgar, 2003a,b; Gião & Godoy, 2007; Gunn & Bird, 2011; Yang & Shiao, 2012; Charabidze et al, 2015; Gunn, 2016; Martin & Verheggen, 2018; but see Bunchu et al, 2008). We also found that individuals of L. sericata and an unidentified platystomatid collected from the traps baited with pig liver tended to have longer antennae than those collected from the other traps.…”
Section: Discussionsupporting
confidence: 69%
“…For example, the oviposition behaviour of Lucilia sericata (Meigen) (Diptera: Calliphoridae) is influenced by two semiochemicals: individuals are initially attracted to sulphur‐rich volatiles, originating from bacterial composition products, and then commence ovipositing in response to ammonia‐rich compounds and carbon dioxide (Ashworth & Wall, 1994). Trap sampling and behavioural assays reveal that the oviposition choices of carrion flies are influenced by the age and body part of the corpse, presence of larval competitors and predators, and location of the corpse on the substrate (Archer & Elgar, 2003a,b; Gião & Godoy, 2007; Gunn & Bird, 2011; Yang & Shiao, 2012; Charabidze et al, 2015; Gunn, 2016; Martin & Verheggen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Even though time taken were not signi icantly different for ground exposed and wrapped control carcasses to reach irst sign of skeletonised stage, it was signi icant under freshwater as wrapping factor delay the decomposition by 2 times. It was explained by Charabidze D et al [38], carcasses with low accessibility took longer to be accessed by the necrophagous lies.…”
Section: Discussionmentioning
confidence: 99%
“…The question of the inside/outside location of a cadaver is a key point in many forensic investigations ( Frost et al, 2010 ). The location of a cadaver affects its colonization time (the pre-appearance interval, i.e., the time before insects reach the cadaver) and thus the post-mortem interval estimation ( Pohjoismaki et al, 2010 ; Reibe & Madea, 2010 ; Charabidze, Hedouin & Gosset, 2015 ). Furthermore, access to the cadaver by necrophagous insects greatly affects its decomposition ( MacLeod & Donnelly, 1962 ; Campobasso, Di Vella & Introna, 2001 ).…”
Section: Spatial Separationmentioning
confidence: 99%